All Days 2014
DOI: 10.2118/171233-ms
|View full text |Cite
|
Sign up to set email alerts
|

Field Study of Temperature Simulators Application for Quantitative Interpretation of Transient Thermal Logging in a Multipay Well

Abstract: Temperature wellbore studies are widely applied for well testing and logging at the stages of exploration and development. However, in nowadays practice the interpretation is still done mainly qualitatively. In last few years different approaches to joint interpretation of temperature along with pressure and flow rates are discussed more and more widely. In particular, there is a special interest in determination of flow profile and individual properties of near-wellbore zone of perforated wells in multi-layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 27 publications
0
1
0
1
Order By: Relevance
“…-Башкирский государственный университет. Аналитические решения для пласта в радиальной постановке для жесткого неоднородного пласта, численные однои двухмерные (R-Z-геометрия) модели для слабосжимаемого пласта, для сильносжимаемого пласта, двухфазные модели [Ramazanov и др., 2010;Valiullin et al, 2014]; -Стэнфордский университет (Stanford University). Исследование и обработка данных неизотермического тестирования скважин с целью извлечения информации о пласте, трещинах или профиле притока ; -Стамбульский технический университет (Istanbul Technical University).…”
Section: Introductionunclassified
“…-Башкирский государственный университет. Аналитические решения для пласта в радиальной постановке для жесткого неоднородного пласта, численные однои двухмерные (R-Z-геометрия) модели для слабосжимаемого пласта, для сильносжимаемого пласта, двухфазные модели [Ramazanov и др., 2010;Valiullin et al, 2014]; -Стэнфордский университет (Stanford University). Исследование и обработка данных неизотермического тестирования скважин с целью извлечения информации о пласте, трещинах или профиле притока ; -Стамбульский технический университет (Istanbul Technical University).…”
Section: Introductionunclassified
“…Under the condition of no layers communication, they found that the temperature response is sensitive to the damaged zone radius and permeability. Valiullin et al (2014) applied similar models to compare the numerical results with field data, as well as the data obtained from deviated wells. The inversion process to achieve multilayer reservoir characterization required all available field data.…”
Section: Introductionmentioning
confidence: 99%